Pengaruh Senam Irama Terhadap Perkembangan Motorik Anak - Aurora Novena Simamora; Grace Putri Sigalingging; Yola Adelina Naipospos; Fransiska Situmorang; Fajar Sidik Siregar (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of motor skills is an important aspect of children's growth, affecting physical skills, muscle coordination, and daily activities. In elementary school, motor development influences children's academic and social abilities. Rhythmic gymnastics is a structured physical activity that can enhance children's motor skills, such as strength, balance, and coordination. This study examines the application of rhythmic gymnastics to improve gross motor skills in elementary school students using literature review and digital research methods. The purpose of this research is to study the impact of rhythmic gymnastics on children's motor development through a literary research approach. The methodology used is a literature review that includes a critical analysis of various academic sources such as journals, books, and relevant articles. The results of the study indicate that rhythmic gymnastics can significantly improve children's gross and fine motor skills. Rhythmic gymnastics activities involving rhythmic movements, coordination, and balance contribute positively to children's physical and cognitive development. Furthermore, rhythmic gymnastics has also been proven effective in enhancing children's social and emotional aspects through enjoyable and structured group activities. These results highlight the importance of incorporating rhythmic gymnastics into the elementary school curriculum to support the development of gross motor skills.